Investigating chemical communication in oribatid and astigmatid mites in bioassays - Pitfalls and suggestions - Michael Heethoff; Günther Raspotnig (Soil Organisms, 2012)
A pair of exocrine opisthonotal oil glands from which more than one hundred chemical compounds have been described characterizes the glandulate Oribatida and the Astigmata. While allomonal and pheromonal properties were demonstrated for some of these compounds in some species, the biological function has remained unknown in most cases. The few existing studies on chemical communication used different kinds of experimental designs with bioassays and impregnated filter paper as source for scent dispersal. Like this, the existence of alarm-, aggregation- and sex-pheromones has been demonstrated. Here, we show that most of these studies may have suffered from some shortcomings regarding two parts of the experimental design: i) proper replication and ii) source for scent dispersal.